2015
DOI: 10.1097/ajp.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Neck Pain are Less Likely to Improve if They Experience Poor Sleep Quality

Abstract: NP is less likely to improve in patients with poorer SQ, irrespective of age, sex, catastrophizing, depression, or treatments prescribed for NP. Future studies should confirm these results with more severely impaired patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…[29] With regard to insomnia, the probability of pain improvement decreases as baseline sleep quality decreases in neck pain patients. [30] Campbell et al [31] found that pain catastrophizing moderated the relationship between sleep efficiency and central sensitization in chronic pain patients. Collectively, although the interaction between depression, anxiety, insomnia, and pain catastrophizing is complex and not fully understood, these psychological factors seem to significantly influence pain perception in chronic pain patients, directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…[29] With regard to insomnia, the probability of pain improvement decreases as baseline sleep quality decreases in neck pain patients. [30] Campbell et al [31] found that pain catastrophizing moderated the relationship between sleep efficiency and central sensitization in chronic pain patients. Collectively, although the interaction between depression, anxiety, insomnia, and pain catastrophizing is complex and not fully understood, these psychological factors seem to significantly influence pain perception in chronic pain patients, directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies in neck pain should incorporate variables reflecting the social domain and other factors that patients perceive as important in their lives (Wiitavaara et al, 2016). Among these are poor sleep quality (Kovacs et al, 2014) , the therapist-patient relationship , expectations of treatment outcome (Skatteboe et al, 2014, economic stress (Palmlof et al, 2012), parental history of musculoskeletal pain (Lier et al, 2014), genetics (Nyman et al, 2011), emotional distress (Johansen et al, 2013), and resilience factors (Sturgeon and Zautra, 2010).…”
Section: Change In Psychological Factorsmentioning
confidence: 99%
“…Many patients suffering from chronic musculoskeletal pain frequently experience sleep problems even when taking analgesics [ 5 , 6 ]. Because insomnia has been shown to worsen pain, mood, and physical functioning, it could negatively impact the clinical outcomes of patients with chronic musculoskeletal pain [ 7 ]. Insomnia is reported to be significantly associated with increased pain intensity and lowered pain threshold [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%